Counter-terrorism policing innovations in Turkey: a case study of Turkish National Police CVE experiment. (27th May 2020) - San, Serdar
ABSTRACT: In recent years, many governments have introduced so-called 'countering violent extremism' (CVE) measures to promote terrorists' and potential terrorists' deradicalization and disengagement from terrorist activity. This paper analyses the potential contribution of CVE programmes to counter-terrorism policing through a case study of Turkey. Drawing on Turkish National Police data from a pilot project in the city of Adana, this study suggests that Turkish CVE measures showed promising results, despite Turkey's history of deterrence-based, repressive, and militarised counter-terrorism policies. The Turkish CVE project pioneered a comprehensive approach to de-radicalisation and disengagement that addresses ideological, social, and practical motivations, and engages clients in every stage of the radicalisation continuum. The paper also analyses Turkey's adoption and later abandonment of the CVE experiment to gauge the policy's broader applicability. While other police forces could adopt the Turkish model, CVE programmes require a democratic political environment and commitment to negotiated resolution of political conflicts.